Comparative Evaluation of Three File Systems for Shaping Curved Canals: An In Vitro Approach - Karuna R. Siraparapu; X. Nagamaheshwari; Veerendra S. Patil; Masuna Rukmini Amulya; Sainath Adsare; Karanam Apoorva Prakash (Journal of Pharmacy and Bioallied Sciences)
Aim: To compare and evaluate the shaping ability of ProTaper Next, TruNatomy, and Flexer heat activation rotary files in simulated curved canals. Materials and Methods: Forty-five severely curved simulated canals in resin blocks were prepared to an apical size of 25 using the following systems (n = 15 per group): ProTaper Next, TruNatomy, and Flexer heat activation. Composite images were made from the superimposition of pre- and post-instrumentation images. Parameters evaluated were total resin removal, centering ability, canal transportation (at the apical, curved, and coronal part), and preparation time. Results: Canals prepared with TruNatomy were better centered in the apical part than those prepared with PTN and Flexer heat activation. Flexer heat activation removed significantly more resin at the outer aspect of the maximum point of curvature. PTN and TruNatomy caused similar canal transportations. Instrumentation with Flexer heat activation required more time than with the two other instruments. Conclusion: Within the limitations of the study, all instruments were safe to use and preserved the original canal shape well. In the apical part of the canals, TruNatomy obtained the best results with regard to canal transportation. Clinical Significance: These findings underscore the importance of considering file selection based on specific canal characteristics and treatment objectives to optimize clinical outcomes in endodontic practice.